Resistance to change: Developing an individual differences measure. - Oreg, Shaul (Journal of Applied Psychology, 2003)
The Resistance to Change Scale was designed to measure an individual's dispositional inclination to resist changes. In Study 1, exploratory analyses indicated 4 reliable factors: Routine Seeking, Emotional Reaction to Imposed Change, Cognitive Rigidity, and Short-Term Focus. Studies 2, 3, and 4 confirmed this structure and demonstrated the scale's convergent and discriminant validities. Studies 5, 6, and 7 demonstrated the concurrent and predictive validities of the scale in 3 distinct contexts. The scale can be used to account for the individual-difference component of resistance to change and to predict reactions to specific change.